2005
DOI: 10.4321/s1130-01082005000200004
|View full text |Cite
|
Sign up to set email alerts
|

Doppler-guided hemorrhoidal artery ligation in the management of symptomatic hemorrhoids

Abstract: Objective: the aim of this study is to clinically test the efficacy of a new approach for patients having symptomatic grade III and IV hemorrhoids. Material and method: 32 patients (17 females) complaining of grade III or IV hemorrhoids were included in the study. A specially designed proctoscope coupled with a Doppler transducer on its tip was used to identify the hemorrhoidal arteries, which were afterwards suture ligated. Operating time as well as per-and postoperative complications were anlyzed. Follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 11 publications
3
35
1
5
Order By: Relevance
“…In a study by Ramirez et al, they also evaluated symptom improvements in patients with grade IV hemorrhoids, who underwent the DGHAL technique and they concluded that most failures occurred in this group (up to 70%). This finding is inconsistent with our study, (8,16) because we observed much better outcomes (no failure), but other elements of Ramirez's study and other studies confirmed our results (4,8,10,17,18). Some studies added some modalities such as recto anal repair adjunct to DGHAL with similar results to DGHAL alone (6,16,19 (20).…”
Section: Discussioncontrasting
confidence: 56%
“…In a study by Ramirez et al, they also evaluated symptom improvements in patients with grade IV hemorrhoids, who underwent the DGHAL technique and they concluded that most failures occurred in this group (up to 70%). This finding is inconsistent with our study, (8,16) because we observed much better outcomes (no failure), but other elements of Ramirez's study and other studies confirmed our results (4,8,10,17,18). Some studies added some modalities such as recto anal repair adjunct to DGHAL with similar results to DGHAL alone (6,16,19 (20).…”
Section: Discussioncontrasting
confidence: 56%
“…In the same year, Ratto et al published the results of the procedure in 35 consecutive patients with more advanced hemorrhoidal disease, obtaining similar data 29 , which suggests that the technique has potential use for the majority of cases with surgical indication 28,29,30,33 . Since then, initial experiments in several countries 5,13,25,27,34 , have been published, with good results, the procedure being isolated or associated with other techniques. Brazil has gaining adherents in recent years, measured by conferences, presentations and publications on initial experience 16,31 ; it showed good results and low complication rates at two years follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Die erreichten Besserungen sind bei allen Untersuchten mit einer Rezidivrate von 1% nach 2 Jahren und 8% nach 5 Jahren relativ stabil. Da bei drittgradigen Hämorrhoiden nur die Hälfte der Patienten eine Besserung verspürte und die Rezidivrate sehr hoch ist (Tabellen 6 und 7), führen wir die HAL im Gegensatz zu anderen Autoren [6,8,21,24] in diesem Stadium nur noch im Ausnahmefall durch.…”
Section: Diskussionunclassified
“…Jedoch wurden entweder sehr kleine Gruppen von 100 und weniger Patienten analysiert [4,6,8,21], oder die Nachbeobachtungszeit betrug einige Wochen bis maximal 1 Jahr [8,15,21,23]. Die Erfolgraten lagen zwischen 59% [21] und 100% [7], auch im Stadium III. Lediglich Tagariello et al [25] (138 Patienten, Nachbeobachtung 2-3 Jahre) und Narro [19] (281 Patienten, Nachbeobachtung 3 Monate bis 2 Jahre) lieferten validere Daten.…”
Section: Introductionunclassified